Agricultural or gardening physical activity may slow neurovascular aging and prevent stroke and dementia: an experimental and cross-sectional study - Kikuchi, Kiyoshi; Takada, Seiya; Otsuka, Shotaro; Nakanishi, Kazuki; Sakakima, Harutoshi; Makizako, Hyuma; Tahara, Nobuhiro; Uchikado, Hisaaki; Shiomi, Naoto; Ooba, Satomi; Matsumoto, Naoyuki; Nishiwaki, Masato (Frontiers in Aging Neuroscience, 2025)
BackgroundAgricultural or gardening activity (also known as hobby farming) is a simple strategy that may be effective for maintaining health and preventing lifestyle-related diseases. However, its preventive effect on the development of conditions associated with neurovascular aging (e.g., stroke and dementia) remains unclear.ObjectiveTo comprehensively investigate the preventive role of regular agricultural or gardening physical activity (AGPA) in neurovascular aging and its underlying mechanisms using two approaches.MethodsWe conducted an experimental study in which we assessed arterial stiffness, cognitive performance (Flanker and Stroop tests), and circulating biomarkers (e.g., plasmin-α2-plasmin inhibitor complexes, nitric oxide, brain-derived neurotrophic factor) in 12 male students (average age: 22 ± 1 years) before and after three 40-min interventions (resting, cycling, and simulated AGPA) under controlled conditions. We also conducted a cross-sectional study, in which we recruited 161 (79 in the AGPA group and 82 in the control group) hospital-based older individuals (average age: 78 ± 5 years) and assessed their history of stroke, cognitive function, and brain magnetic resonance imaging (MRI) findings.ResultsIn the experimental study, simulated AGPA reduced arterial stiffness, improved executive cognitive function, and elevated circulating plasmin-α2-plasmin inhibitor complexes, nitric oxide, and brain-derived neurotrophic factor. Brain MRI-assessed cerebral white matter hyperintensities caused by reduced blood flow to brain tissue and stroke prevalence were lower, and cognitive scores (as assessed by the Hasegawa Dementia Scale-Revised) were higher in the AGPA group than in the control group.ConclusionOur findings suggest that regular AGPA is associated with markers of slower neurovascular aging in older individuals. AGPA induces a combination of general physical activity-related and specific AGPA-related effects; moreover, it may offer similar or even greater benefits than physical activity alone. Therefore, habitual AGPA may serve as an effective preventive strategy for neurovascular aging.